IMPROVING STUDENTS’ SPEAKING SKILL AT GRADE X AT SMA NURUL HASANAH TEMBUNG THROUGH COMMUNITY LANGUAGE LEARNING METHOD - Dwi Suci Amaniarsih; Juliana Juliana; Erni Darmayanti (Universitas Dharmawangsa, 2022)
ABSTRACT - This study aims to determine the application of the Community Language Learning method in improving students' speaking skills in English. The research was conducted on students of grade X SMA Nurul Hasanah Tembung. Based on the percentage of completeness of student learning outcomes, it can be seen that at the stage of the first cycle, the mastery of student learning outcomes was obtained by 65% and in the second cycle, the mastery of students’ learning outcomes increased to 74%. While the average value of the two cycles shows that there are 23 students (74%) who experience completeness, while as many as 8 students (26%) do not experience completeness in the students' English speaking skills using the Community Language Learning method. Thus, it can be stated that this research is successful and it is proven that the use of the Community Language Learning method can improve students' English speaking skills. where 70% of the total number of students can follow the learning process well and have achieved an average score of 70.Keywords: Speaking Skills, English, Community Language Learning Method